SiO2‐modified nanocomposite nanofiltration membranes with high flux and acid resistance. Issue 18 (11th January 2019) - Wei, Xiuzhen; Xu, Xufeng; Wu, Jiawei; Li, Cuixia; Chen, Jinyuan; Lv, Bosheng; Zhu, Baoku; Xiang, Hai
ABSTRACT: Thin‐film nanocomposite (TFN) nanofiltration (NF) membranes with superior properties were prepared using hydrophilic SiO2 (HGPN‐SiO2 ) nanoparticles as the inorganic modifying monomer by an interfacial polymerization (IP) process. The effects of HGPN‐SiO2 on the morphology and surface properties of the prepared NF membranes were characterized by attenuated total reflectance–Fourier transform infrared spectroscopy, field emission scanning electron microscopy, X‐ray photoelectron spectroscopy, atomic force microscopy, surface zeta potential, and static contact angle. The addition of HGPN‐SiO2 can effectively improve the permeate flux of the NF membranes. When the HGPN‐SiO2 concentration in the aqueous phase was 0.08 wt %, the permeate flux of the TFN‐NF membrane was twice that of the pure NF membrane. Furthermore, the acid resistance of the TFN‐NF membrane was clearly improved with the addition of HGPN‐SiO2 . Under neutral conditions, the TFN‐NF membrane showed superior flux and salt rejection stability in a long‐running operation. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47436. Abstract :